2009
DOI: 10.1007/s11229-009-9553-5
|View full text |Cite
|
Sign up to set email alerts
|

Intentions and interactive transformations of decision problems

Abstract: In this paper I study two ways of transforming decision problems on the basis of previously adopted intentions, ruling out incompatible options and imposing a standard of relevance, with a particular focus on situations of strategic interaction. I show that in such situations problems arise which do not appear in the single-agent case, namely that transformation of decision problems can leave the agents with no option compatible with what they intend. I characterize conditions on the agents' intentions which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…I have completely axiomatized [913] 312 Synthese (2009) 171:291-320 this system and used it to further the work on intention-based transformation of decision problem initiated by van Hees and Roy (2008) and Roy (2009), by answering four questions left open by their approach. All in all, I have provided a framework that merges insights from and contributes to three strong traditions in the study of rational agency: dynamic epistemic logic, epistemic game theory and philosophy of action.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…I have completely axiomatized [913] 312 Synthese (2009) 171:291-320 this system and used it to further the work on intention-based transformation of decision problem initiated by van Hees and Roy (2008) and Roy (2009), by answering four questions left open by their approach. All in all, I have provided a framework that merges insights from and contributes to three strong traditions in the study of rational agency: dynamic epistemic logic, epistemic game theory and philosophy of action.…”
Section: Resultsmentioning
confidence: 99%
“…I have answered four questions left open by van Hees and Roy (2008) and by Roy (2009). I first showed that cleaning corresponds to a public announcement of "intention-rationality" under common knowledge of intentions.…”
Section: Corollary 3 Suppose That For a Pointed Model M W The Announmentioning
confidence: 96%
See 3 more Smart Citations